2021
DOI: 10.3390/ijerph182312468
|View full text |Cite
|
Sign up to set email alerts
|

Scientometric Analysis of Global Scientific Literature on Aging in Place

Abstract: The amount of literature reporting “aging-in-place” studies has increased sharply in recent decades. However, the studies have taken a global view of the range and scope of the research that has taken place. This study presents a bibliometric analysis of the current status of the aging in place research themes published as scientific articles between 1970 and 2021, using the Web of Science database. VOSviewer software was employed to map and visualize the 1331 items of bibliographic data retrieved. The finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 63 publications
0
15
0
Order By: Relevance
“…The USA ranked first in both the number of publications and C/P, indicating its dynamic status in this field. This may be because of its “active aging society and high rates of funding for research“ [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The USA ranked first in both the number of publications and C/P, indicating its dynamic status in this field. This may be because of its “active aging society and high rates of funding for research“ [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…For analysis, the study used the WoS database developed by Clarivate Analytics in the United States, which is a web-based database allowing users to search academic materials published after 1900. It contains a comprehensive database of literature from influential papers and has the most reliable downloading capabilities [ 19 ]. In the current research, we used the Core Collection database in WoS with “All” editions in Core Collection, which includes databases published in SCI-Expanded, SSCI, A&HCI, CPCI-S, CPCI-SSH, and ESCI indexes.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the past century, scientometrics research has progressed from the unconscious to consciousness, from qualitative to quantitative research, and from outward description to a thorough examination of the fundamental characteristics of scientific production. Recent research has shown the effectiveness of scientometrics in a variety of fields, including additive manufacturing [ 38 , 39 , 40 ], data analysis [ 94 , 95 ], built environment [ 96 , 97 , 128 , 129 ], research impact [ 131 ], sustainability [ 132 , 133 ], energy [ 134 ], project management [ 135 ], construction [ 136 , 137 ], water supply [ 138 , 139 ], medical applications [ 99 , 100 , 101 , 140 , 141 ], visualisation of data [ 103 , 104 , 105 , 106 , 107 , 108 , 114 , 115 , 116 , 117 , 118 ], and author collaborations [ 142 , 143 , 144 ]. Modern scientometric analysis enables researchers to access scientific contributions, map knowledge structures, to access scientific advancement, and identify emerging patterns within a certain study subject from these literature studies.…”
Section: Methodsmentioning
confidence: 99%